ASSESSMENT-BASED MATERIAL DEVELOPMENT: USING STUDENTS’ WORKS FOR DEVELOPING ENGLISH LEARNING MATERIAL - Kristiandi Kristiandi; Hefy Sulistyawati; Dewi Cahyaningrum (UAD TEFL International Conference)
Despite the vital role of teachers in delivering English instructions, English learning material takes the most prominent role in the learning process. As English learning process is expected to be learning centered, the role of English learning material becomes more strategic and crucial in fostering students’ learning. With the adopted curriculum as the framework and the concept of authentic materials as the basis, the development of English learning material needs to incorporate students’ learning problems and expectations. As such, teachers as learning facilitators are supposed to be alert to students’ needs for learning as well as their expectations and use them to update the learning materials as learning takes place. Students’ worksheets, which are the reflection of their current inter-language, are very good resource for teachers in developing a series of updated English learning materials and relevant communicative activities which are student-friendly. Developed on the revised Communicative Language Teaching (CLT) approach and Krashen’s Input Hypothesis, this paper highlights the importance of accommodating students’ learning problems for developing English learning materials by using formative and summative assessments results within a period of an English instructional program